Title Preservation of Tshidzimba, a cereal-legume composite porridge, through fermentation, canning and drying - Taylor, J.R.N. (John Reginald Nuttall) (University of Pretoria, 2013)
Dissertation (M Inst Agrar ( Food Processing))--University of Pretoria, 2006.